The Puritan experiment : New England society from Bradford to Edwards - Bremer, Francis J. (Hanover : University Press of New England, 1995)
The comprehensive history of a system of faith that shaped the nation.
11 Challenges to the Faith: Pluralism and Declension12 An Oppressed People: New England's Encounters with Metacom, Governor Andros, and the Witches; 13 Art and Science in Colonial New England; 14 Race Relations; 15 New Directions: Puritanism in the Neglected Decades; 16 Enlightenment and Evangelicalism; Suggestions for Further Reading; Index.
Includes bibliographical references (pages 234-247) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Puritans -- New England; New England -- History -- Colonial period, ca. 1600-1775.; Puritains -- Nouvelle-Angleterre.; Nouvelle-Angleterre -- Histoire -- ca 1600-1775 (Période coloniale); HISTORY -- State & Local; HISTORY -- State & Local -- General; HISTORY / General; Puritans; New England; Puritanismus; Neuengland; Puritanisme; 1600-1775; History